Effects of Experience on Teachers’ Self-Efficacy in Secondary Schools - Odanga, Sylvester JO; Aloka, Peter JO; Raburu, Pamela (Alberta Journal of Educational Research, 2022)
The present study investigated the effects of teaching experience on teachers’ self-efficacy in Kenyan secondary schools. The study used a sequential explanatory design and the Teacher Self-Efficacy Scale. This scale consisted of a total of 24 items with eight items measuring each of the three domains of teacher self-efficacy: student engagement, instructional strategies, and classroom management. The face and content validities of the modified Teacher Self-Efficacy Scale were ascertained by two experts in Educational Psychology from a Kenyan university. The sample size of the study comprised 327 teachers obtained using stratified random sampling technique. The quantitative data was analyzed using Multivariate Analysis of Variance (MANOVA) but qualitative data from interviews was analyzed thematically. The MANOVA results demonstrate that the effects of experience on teachers’ self-efficacy was significant, Wilk’s λ (7, 319 = 0.945, p = 0.019). The article concludes that Kenyan Teachers’ Service Commission should utilize experienced teachers as resource persons who are attached to several schools. Key words: Experience, Teachers’ Self-Efficacy, Secondary Schools La présente étude a examiné les effets de l'expérience d'enseignement sur l'auto-efficacité des enseignants dans les écoles secondaires du Kenya. L'étude a utilisé un plan explicatif séquentiel et l'échelle d'auto-efficacité des enseignants. Cette échelle comprend un total de 24 éléments, dont huit mesurent chacun des trois domaines d'auto-efficacité des enseignants : l'engagement des élèves, les stratégies d'enseignement et la gestion de la classe. Les validités de face et de contenu de l'échelle modifiée d'auto-efficacité de l'enseignant ont été vérifiées par deux experts en psychologie de l'éducation d'une université kenyane. L'échantillon de 327 enseignants a été obtenu par la technique d'échantillonnage aléatoire stratifié. Les données quantitatives ont été analysées à l'aide de l'analyse multivariée de la variance (MANOVA), mais les données qualitatives issues des entretiens ont été analysées de manière thématique. Les résultats du MANOVA démontrent que les effets de l'expérience sur l'auto-efficacité des enseignants étaient significatifs, Wilk's λ (7, 319 = 0.945, p = 0.019). L'article conclut que la Kenyan Teachers' Service Commission devrait utiliser des enseignants expérimentés comme personnes ressources qui sont attachés à plusieurs écoles. Mots clés: expérience, auto-efficacité des enseignants, écoles secondaires.